Digital-wavelength ytterbium fiber laser mode-locked with MoS2. (1st April 2016) - Wang, Shiwei; Zhou, Yan; Wang, Yao; Yan, Shuo; Li, Yue; Zheng, Wanguo; Deng, Ying; Zhu, Qihua; Xu, Jianqiu; Tang, Yulong
Abstract: In this letter, we report a digital-wavelength ytterbium-doped fiber laser passively mode-locked with layered molybdenum disulfide (MoS2 ). The MoS2 based saturable absorber (SA) is made by solution coating the MoS2 solution on a gold mirror, showing modulation depth and saturation intensity of 11.4% and 1.37 MW cm −2, respectively. The output pulse has duration of ~300 ps, 3 dB spectral width of ~0.5 nm and maximum output power of 2.6 mW. The mode-locked fundamental frequency is 2.67 MHz with a ~36 dB signal-to-noise ratio. Through tuning the polarization controller (PC) and squeezing/stretching the single mode fiber in the ring cavity, four-bit digital wavelength emission is achieved. It is proposed that the digital-wavelength tuning feature of fiber lasers can be employed in coding and signal processing.